Impacts of the Cow Dung Biochar to the Soil Fertility - Davaapurev, Nandintsetseg; Battulga.G; Sarantuya.S; Battsetseg.G, (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
We have encountered a number of global ecological problems as reducing greenhouse gases, creating green mining, mitigating soil desertification and maintaining natural balance. Our country is the country of animal husbandry and one of our ecological problems is processing the animal waste and using it as organic raw material. Therefore, we studied the properties of the biochar produced from cow dung in Mongolia in order to study its impacts to the soil.The United Nations Organization organizes annual forums on climate changes and one of the discussions in 2014 was bio-coal: a proposal on using the bio-coal as one of the technologies to mitigate climate change and to acclimatize it [1-3].Biochar is a black residue of biomass hot decomposition. Biochar is a substance resulted from hot processing, has aromatic structure and contains mainly carbon; its chemical and biological properties ensure it as strongly reliable material (adsorbent) with much surface, high degree of porosity and good ability to absorb different substances in liquid, solid and gas mode [4-6].Therefore, studied the properties of the biochar, which was produced from such common waste in Mongolia as cow dung, and studied its impacts to the soil.